Pistas, saídas, fugas e suspeições da escola como agenciamento de uma matriz discursiva da vulnerabilidade - Heman, Marília Rodrigues Lopes (2020)
This Master's Dissertation bound to PPGE - Graduate Program in Education, CE - Education Center, from Federal University of Santa Maria (UFSM), Research Line LP3 - Special Education, inclusion and difference, and GEPE - Study and Research Group on Special Education and Inclusion, with the theme of thinking about vulnerability in the field of Education, in times of inclusion. As a research problem, we establish the following question: How can a discourse-notion of vulnerability be constituted in a matrix of enunciative experience managed at school to situate school subjects? And, as a general objective: To analyze how State policies and scientific productions can produce a discourse-notion in a discursive matrix of vulnerability, which sets up strategies to manage the performance of schoolchildren/vulnerable subjects at school. We constitute the specific objectives of the research from the methodological steps that, in an intensive and connective way, guide the accomplishment of a data survey in some documents: the political-legal ones - the State policies - and the scientific productions. It is from this connection that the possibilities of naming vulnerability discursively in the present were approaching. Plus, the choice of developing based-on-contemporary-philosophy research enables the analysis, placing the production of truth as contingent and linked to the historical conditions of the present. The path that generates the analytical substrate, in turn, entwined some operators (GALLO, 2006), in a network of thoughts, in which conceptual operators allow, through the appropriation of some notions, a way of organizing thinking to think about vulnerability. These notions came from contemporary authors, among them: Deleuze and Guattari. Moreover, we develop, by the analysis tools-concepts analysis, the procedural operators, by the notions to seek to operate amid the resolution of the research question and objectives, and which are close to what we identify throughout the investigation and the production of analytical materiality. The procedural operators moved away from Foucault's thinking as a way of operating the analyzes, based on concepts signed by him, namely: knowledge and power. As a result, the production of analytical materiality, based on materials, resulted in two analytical focuses: that of the enunciative experience of the vulnerability's discursive matrix, and that of the school as an agency of the vulnerability's discursive matrix. Thus, we systematize a brief conclusion in which not only territoriality, deterritorialization but also reterritorialization rivalries are the 'spaces' in which, based on the identified clues, the movements of discursive events of State policies, which we organize in risk analytical units, are located, exclusion and lack, and in the relations of scientific productions connected to State policies, which we organize in the analytical units, the individual, the social and the institutional; and, events of thought produced by the investigative movements from the identification of a truth policy that places an immanent condition of knowledge and power, namely: [marginalization to health, school, and justice]; [attempt to erase social inequalities]; [State's liability process]. Still, the identity that invents, moves, and transforms the school, through its [consensual judgment of educational practices for...] the [teacher/subject/product].